Iman Kristen Dan Kebudayaan - Sundoro Tanuwidjaja; Samuel Udau (Jurnal Teologi Kontekstual Indonesia, 2020)
Culture is created by God, as it is the essence of Christian faith, in order to reflects His values and glory. Culture can not be separated from the existence of God relate to its origin, process and ultimate objective. However, culture is never be able separated from humanity's oldest struggle, sin. The existence of sin also takes part in various area in the development of human culture, there for brings those who insult and assume that God is not the highest and must be glorified, even rejecting the existence of God. The teachings of the Christian faith explain the concept of redemption which finally enables the culture to recognize the existence of God as the highest being, and to reveal His glory. This paper expresses various Christian struggles in addressing the existence and development of human culture from the perspective of the Christian faith, and returning it to God's original position and purpose for humans. Kebudayaan berasal dari Allah dijalankan sesuai tata nilai dari Allah dan dan harus kembali kepada Allah, itulah esensi iman Kristen. Budaya tidak dapat dipisahkan dari keberadaan Allah, baik asal mulanya, prosesnya hingga kepada tujuan akhirnya. Walau demikian, kebudayaan tidak terlepas dari pergumulan tertua manusia, yaitu dosa. Keberadaan dosa juga mengambil andil dalam perkembangan kebudayaan manusia ke berbagai bidang, sehingga ada yang melecehkan dan mengganggap bahwa Allah bukanlah yang tertinggi dan harus dimuliakan, bahkan menolak keberadaan Allah. Ajaran iman Kristen memaparkan konsep penebusa yang akhirnya memampukan kebudayaan itu mengakui keberadaan Allah sebagai Pribadi yang tertinggi, dan menyatakan kemuliaan-Nya. Tulisan ini mengungkapkan berbagai pergumulan orang Kristen dalam menyikapi keberadaan maupun perkembangan kebudayaan manusia dari sudut pandang iman Kristen, dan mengembalikannya pada posisi maupun tujuan awal Allah bagi manusia.